2001
DOI: 10.1021/ol0159367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chemical Diversity of Epoxyquinoid Natural Products:  Synthesis and Biological Activity of (−)-Jesterone and Related Molecules

Abstract: Enantioselective syntheses of the potent antifungal agent (-)-jesterone, its hydroxy epimer, and a dimeric quinone epoxide derivative are reported. The synthesis involves diastereoselective epoxidation of a chiral quinone monoketal derivative and regio- and stereoselective reduction of a quinone epoxide intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 24 publications
3
59
0
Order By: Relevance
“…Chemical biology of inflammatory cytokine signaling T Kataoka epoxyquinol B, 88 epoxyquinone A monomer, 87 jesterone dimer, 89,90 manumycin A 60 and panepoxydone, 91 have been reported to inhibit NF-kB activation. Epoxyquinoids contain the epoxide structure that is known to react with nucleophiles, such as cysteine thiol groups.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical biology of inflammatory cytokine signaling T Kataoka epoxyquinol B, 88 epoxyquinone A monomer, 87 jesterone dimer, 89,90 manumycin A 60 and panepoxydone, 91 have been reported to inhibit NF-kB activation. Epoxyquinoids contain the epoxide structure that is known to react with nucleophiles, such as cysteine thiol groups.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
“…94 Jesterone dimer (Figure 5a), which was reported to exert 10-to 100-fold greater antitumor activity than jesterone, has been shown to block TNF-ainduced IKK activation. 89,90 Indeed, jesterone dimer converts constitutively active IKKb into stable higher molecular mass forms, irrespective of its Cys-179 mutation (Figure 5b). 90 It has also been shown that epoxyquinol B is able to bind covalently to cysteine residues of several proteins and to crosslink proteins through the cysteine residues by opening its epoxide ring.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
“…2 On the other hand, epoxyquinol B (2) is a homodimer of 14a, which would be generated by an exo intermolecular Diels-Alder reaction, also with the sterically favored anti stereochemistry at the C9 and C19 methyl positions. 3 In their recent elegant total synthesis of torreyanic acid 19 and jesterone dimer (unnatural product), 54 Porco, Jr. et al have demonstrated the oxidative dimerization of epoxyquinones, in which only heterodimers form. As shown in the dimerization of (+)-5, not only epoxyquinones, but also epoxycyclohexenones can be oxidatively dimerized to form highly functionalized heptacyclic ring systems, in which both heteroand homo-dimerization occur.…”
mentioning
confidence: 99%
“…We have been synthesizing and studying the bioactivity of several epoxyquinoids. For example, we have reported previously the total synthesis of the natural metabolites jesterone from Pestalotiopsis jesteri, cycloepoxydon from the Deuteromycetes strain 45-93, and epoxyquinol A from an uncharacterized fungus (Hu et al, 2001;Li et al, 2001aLi et al, , 2002.…”
mentioning
confidence: 99%
“…1) kills tumor cells with IC 50 values ranging from approximately 100 to 500 M in three different human tumor cell lines (Hu et al, 2001). However, a dimeric derivative of jesterone, which we have termed "jesterone dimer" (JD) (Fig.…”
mentioning
confidence: 99%